Impact of territory management on urban flood: a test case - Cinosi, Jacopo; Pasculli, Antonio; Sciarra, Nicola (Italian journal of engineering geology and environment, 2019)
<span data-sheets-value="{"1":2,"2":"The maintenance of the territory, through the recovery of the water courses even at the scale of small canals, from any type of obstruction, in particular weeds, tree trunks, all kinds of debris that prevent the natural and correct drainage of rainwater, constitutes an important need for flood prevention, even for small urban scale located in small hydrological basins. For a correct evaluation of the actions to be implemented, the application of advanced computational tools, beside expert judgment, appear to be not only useful, but also necessary. For this purpose, different numerical tools have been proposed. Among these, the mathematical approach of the 'Shallow water', based on the Finite Element Method and the Godunov-Riemann technique, used in the commercial computational code, selected in this paper, is very popular within the international context. Moreover, the selected commercial software is based on the Graphical Processing Unit (GPU), which can reduce the calculation times even by 80 times. The case study used in this article concerns a rainy event that occurred between April 26th and May 2nd, 2014 that caused flooding between May 2nd and 3rd in the Pianello di Ostra district in the province of Ancona (Marche, Italy). After an opportune site inspection and the relative useful interview of the inhabitants of the place, a topographic high resolution survey (30 cm x 30 cm) was carried out by means of a drone. Then GIS and the available cartography were used, while the pluviometric data were taken from the available website, relating to the Corinaldo Station about 9.1 km from Pianello d’Ostra. The rainfall data were processed using the Curve-Number (CN) empirical method, developed by the USDA Natural Resources Conservation Service (SCS). The method allows to determine the approximate amount of runoff in small basins, consequent to a given precipitation, also considering the specific characteristics of the area concerned. Several parametric simulations have been carried out considering, in particular, the state of maintenance of the Fosso della Trocca that characterizes the basin under study, with and without the presence of debris. Furthermore, the effect of the presence of a small crossing bridge was also considered. The calibration of the model was obtained considering the pre-event state of the canal and of the small bridge, that was affected by debris, and confirming by a numerical point of view, the urban flood occurrence, with heights of the surface of the water comparable to that actually occurred. (15-50 cm). Finally, considering the current conditions of the channel and the removal of the small bridge, the numerical simulation predicts that, with the same rainfall conditions, the flooding would not have occurred."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">The maintenance of the territory, through the recovery of the water courses even at the scale of small canals, from any type of obstruction, in particular weeds, tree trunks, all kinds of debris that prevent the natural and correct drainage of rainwater, constitutes an important need for flood prevention, even for small urban scale located in small hydrological basins. For a correct evaluation of the actions to be implemented, the application of advanced computational tools, beside expert judgment, appear to be not only useful, but also necessary. For this purpose, different numerical tools have been proposed. Among these, the mathematical approach of the 'Shallow water', based on the Finite Element Method and the Godunov-Riemann technique, used in the commercial computational code, selected in this paper, is very popular within the international context. Moreover, the selected commercial software is based on the Graphical Processing Unit (GPU), which can reduce the calculation times even by 80 times. The case study used in this article concerns a rainy event that occurred between April 26th and May 2nd, 2014 that caused flooding between May 2nd and 3rd in the Pianello di Ostra district in the province of Ancona (Marche, Italy). After an opportune site inspection and the relative useful interview of the inhabitants of the place, a topographic high resolution survey (30 cm x 30 cm) was carried out by means of a drone. Then GIS and the available cartography were used, while the pluviometric data were taken from the available website, relating to the Corinaldo Station about 9.1 km from Pianello d’Ostra. The rainfall data were processed using the Curve-Number (CN) empirical method, developed by the USDA Natural Resources Conservation Service (SCS). The method allows to determine the approximate amount of runoff in small basins, consequent to a given precipitation, also considering the specific characteristics of the area concerned. Several parametric simulations have been carried out considering, in particular, the state of maintenance of the Fosso della Trocca that characterizes the basin under study, with and without the presence of debris. Furthermore, the effect of the presence of a small crossing bridge was also considered. The calibration of the model was obtained considering the pre-event state of the canal and of the small bridge, that was affected by debris, and confirming by a numerical point of view, the urban flood occurrence, with heights of the surface of the water comparable to that actually occurred. (15-50 cm). Finally, considering the current conditions of the channel and the removal of the small bridge, the numerical simulation predicts that, with the same rainfall conditions, the flooding would not have occurred.